Tracer Study of Faculty of Economics and Business Alumni : To What Extent Are Graduates Categorized as Qualified? - Nadia Asandimitra Haryono; Febrika Yogie Hermanto; Cahya, Septyan Budy; Ladi Wajuba Perdini Fisabilillah; Khusnul Fikriyah; Vivi Pratiwi; Insyirah Putikadea; Amirusholihin Amirusholihin; Veni Rafida; Rasyidi Faiz Akbar; Fresha Kharisma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Tracer study of Surabaya State University has been conducted in each study program in order to fulfill accreditation needs. Instrument development is still carried out independently at the study program and faculty levels so that the disparity of instruments in each faculty is very high. This study will later aim to create an effective alumni tracing model in achieving a response rate. Because in several universities throughout Indonesia, a superior model has not been found and detailed properly. The type of research used is descriptive qualitative. The population in this study were graduates of the Faculty of Economics and Business, Universitas Negeri Surabaya who had obtained diplomas throughout 2022. The sample used was a saturated sample considering that this study aims to explore graduate data related to careers. The results showed that the response rate reached 100%, with more than 67.8% of graduates getting jobs in less than six months with an income of at least 1.2 times the UMP, exceeding the institution's target. This tracer study plays an important role in evaluating the quality of graduates and the relevance of education to the world of work. These findings provide a basis for improving the curriculum and quality of education at Universitas Negeri Surabaya.